Pengaruh Terapi Sholat Dhuha Terhadap Penurunan Tekanan Darah pada Lansia di Pantai Sosial Tresna Werdha Provinsi Nusa Tenggara Barat - Istiana, Dian; Sukma Purqoti, Dewi Nur; Romadonika, Fitri; Pusparini, Mita (Sekolah Tinggi Ilmu Kesehatan YARSI Mataram, 2021)
Hypertension, also known as the sillet killer, is a non-communicable disease that is quite dominant in the world in both developed and developing countries. Hypertension shows blood pressure levels above normal limits. Hypertension is often found in the elderly. The factors that make the elderly suffer from hypertension are genetic and environmental factors. Genetic factors affect sensitivity to sodium, sensitivity to stress, reactivity of blood vessels to vasoconstrictors, insulin resistance and others. Meanwhile, environmental factors include diet, smoking habits, emotional stress, and obesity. This study aims to determine the effect of dhuha prayer therapy on reducing blood pressure in hypertensive elderly at the Tresna Werdha Social Home, West Nusa Tenggara Province. This study used quasi-experimental research design with one group pre-test post-test design (pre-test design in one group, no comparison / control group). The sample in this study were 16 people. Based on the results of the analysis using the dependent t test, it was found that the value of p = 0.00 (p <0.05), so it can be concluded that there is an effect of dhuha prayer therapy on reducing blood pressure in elderly people with hypertension. After the implementation of this research activity, it is hoped that